(untitled) (Bangladesh Journal of Microbiology, 2016)
Bacillus cereus TC-1 was isolated from condenser pond of manmade solar salt pan Thamaraikulam, Tamilnadu, India effectively suppressed the shrimp bacterial pathogens Vibrio harveyi, V. parahaemolyticus, V. anguillarum, V. alginolyticus and V. vulnificus by in vitro antagonistic assay of 9 to 15 mm of zone of inhibition. Phylogenetic analysis revealed that, B. cereus TC-1 was highly similar that the B. thuringiensis strain (100%) and other Bacillus sp. Their optimum growth between at the range of 4 to 6% of NaCl in the growth media and significantly (P<0.05) high alkaline protease production (170.85 U/ml) was observed in the NaCl of 6 %. Based on the antagonistic activity of the B. cereus TC-1 against the shrimp pathogens and its antimicrobial factors, it may be used as probiotics and developing novel antimicrobial bioactive substances against aquatic pathogens. Bangladesh J Microbiol, Volume 29, Number 1, June 2012, pp 27-31